Processes of fragmentation in the Amboseli ecosystem, Southern Kajiado district, Kenya - BurnSilver, S.B.; Worden, J.; Boone, Randall B. (Springer, 2008)
The Amboseli ecosystem is known worldwide as one of Kenya’s “conservation jewels,” and is recognized as a landscape where humans, livestock, and wildlife have co-existed for centuries. However, there is a long-term shift underway, pushed by a transition in human land-use from extensive pastoralism by Maasai to intensive pastoralism carried out within legally-prescribed private parcels of land. In the face of this transition, the region’s wildlife populations and its system of seasonal livestock and wildlife movements appear increasingly fragile, and Maasai pastoralists themselves are facing significant challenges to their economic and cultural well-being.